2008
DOI: 10.1104/pp.108.128199
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of OsbZIP23 as a Key Player of the Basic Leucine Zipper Transcription Factor Family for Conferring Abscisic Acid Sensitivity and Salinity and Drought Tolerance in Rice  

Abstract: OsbZIP23 is a member of the basic leucine zipper (bZIP) transcription factor family in rice (Oryza sativa). Expression of OsbZIP23 is strongly induced by a wide spectrum of stresses, including drought, salt, abscisic acid (ABA), and polyethylene glycol treatments, while other stress-responsive genes of this family are slightly induced only by one or two of the stresses. Transactivation assay in yeast demonstrated that OsbZIP23 functions as a transcriptional activator, and the sequences at the N terminus (amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
410
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 607 publications
(463 citation statements)
references
References 67 publications
32
410
1
4
Order By: Relevance
“…Rice seedlings overexpressing ZFP179 possess enhanced expression of DREB2A, which acts ABA-independently (Dubouzet et al, 2003). Furthermore, overexpression of bZIP23, ZFP179, and ZFP252, genes that did not respond to salt stress in serf1 roots (Figure 4), increases expression of LEA3 (Xiang et al, 2008;Xu et al, 2008;Sun et al, 2010). Although LEA3 expression is ABA dependent, it is affected by the impaired H 2 O 2 signaling in serf1, probably due to the lack of response(s) of upstream regulator(s).…”
Section: Discussionmentioning
confidence: 99%
“…Rice seedlings overexpressing ZFP179 possess enhanced expression of DREB2A, which acts ABA-independently (Dubouzet et al, 2003). Furthermore, overexpression of bZIP23, ZFP179, and ZFP252, genes that did not respond to salt stress in serf1 roots (Figure 4), increases expression of LEA3 (Xiang et al, 2008;Xu et al, 2008;Sun et al, 2010). Although LEA3 expression is ABA dependent, it is affected by the impaired H 2 O 2 signaling in serf1, probably due to the lack of response(s) of upstream regulator(s).…”
Section: Discussionmentioning
confidence: 99%
“…8B). To further exclude the possibility of OsPP18 on ABA signaling, the expression of a few well-known ABA-responsive genes in rice, including RESPONSIVE TO ABA PROTEIN21 (RAB21), LOW TEMPERATURE INDUCED PROTEIN9 (LIP9), and Osb-ZIP23 (Mundy and Chua, 1988;Rabbani et al, 2003;Xiang et al, 2008), was checked in the ospp18 mutant. The qPCR results indicated that the ABA-induced expression of these genes was not affected in the ospp18 mutant (Fig.…”
Section: Ospp18 Functions Independent Of Aba Signalingmentioning
confidence: 99%
“…OsABI5, named according to its homology to ABI5 in Arabidopsis, was suggested to be involved in ABA signal transduction and stress responses (Zou et al, 2007(Zou et al, , 2008. OsbZIP23 was characterized as a key player of the bZIP family for conferring ABA sensitivity, salinity, and drought tolerance of rice (Xiang et al, 2008). Several other members were also mentioned for their involvement in ABA and stress (Zou et al, 2007;Lu et al, 2009;Amir Hossain et al, 2010).…”
mentioning
confidence: 99%
“…Several members have been studied for their functions potentially related to stress responses, such as LIP19 (Shimizu et al, 2005), OsBZ8 (Nakagawa et al, 1996;Mukherjee et al, 2006), and RF2a and RF2b (Dai et al, 2004(Dai et al, , 2008. Noticeably, in contrast to the comprehensive studies of ABFs in Arabidopsis, mainly three members of the third subfamily in rice, TRAB1, OsABI5, and OsbZIP23, have been studied for their roles in ABA-mediated stress responses (Hobo et al, 1999;Xiang et al, 2008;Zou et al, 2008). TRAB1, which is identified by yeast two-hybrid screening for proteins that interact with the seed development-related transcription factor VP1, can be activated by ABA-dependent phosphorylation in its Ser-102 residue (Hobo et al, 1999;Kagaya et al, 2002;Kobayashi et al, 2005), but its biologic function remains to be clarified.…”
mentioning
confidence: 99%